2011
DOI: 10.1182/blood-2011-02-339432
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinetically quiescent (G0/G1) human multiple myeloma cells are susceptible to simultaneous inhibition of Chk1 and MEK1/2

Abstract: Effects of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
43
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 48 publications
2
43
0
Order By: Relevance
“…Many inhibitors targeting DNA repair pathways (PARP1, DNA-PK, ATM, ATR, MGMT, APE) or cell-cycle checkpoints (CHK1, CHK2) have now been developed and might be useful to induce tumor cell apoptosis in combination with DNA damage-inducing drugs. [25][26][27][28][29][30] Herein, to further investigate the mechanistic basis for the link between DNA repair efficiency and response to antimyeloma therapy, we studied major DNA repair mechanisms in MM cell lines and malignant bone marrow plasma cells (BMPCs) from patients with MM before antimyeloma therapy. We found that BMPCs from responders to melphalan therapy are characterized by slower rates of NER and DSBs repair (DSB/R) compared with nonresponders.…”
Section: Introductionmentioning
confidence: 99%
“…Many inhibitors targeting DNA repair pathways (PARP1, DNA-PK, ATM, ATR, MGMT, APE) or cell-cycle checkpoints (CHK1, CHK2) have now been developed and might be useful to induce tumor cell apoptosis in combination with DNA damage-inducing drugs. [25][26][27][28][29][30] Herein, to further investigate the mechanistic basis for the link between DNA repair efficiency and response to antimyeloma therapy, we studied major DNA repair mechanisms in MM cell lines and malignant bone marrow plasma cells (BMPCs) from patients with MM before antimyeloma therapy. We found that BMPCs from responders to melphalan therapy are characterized by slower rates of NER and DSBs repair (DSB/R) compared with nonresponders.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 We have published several studies combining SRC/MEK1/2 inhibitors with CHK1 inhibitors in established tumor cell types, notably breast cancer cells, but not in CNS tumor cells that are generally thought to be much more resistant to many therapeutic modalities, and demonstrated that the lethality of CHK1 inhibitors is enhanced by their combination with inhibitors of the SRC-RAS-MEK1/2-ERK1/2 pathway. [9][10][11][12][13][14] Treatment of tumor cells with CHK1 inhibitors enhances signaling through the SRC-RAS-MEK1/2-ERK1/2 pathway and expression of a dominant negative CHK1 protein elevates basal ERK1/2 activity and blocks CHK1 inhibitor-induced ERK1/2 activation. [9][10][11][12][13][14] Interruption of MEK1/2-ERK1/2 pathway by MEK1/2 inhibitors dramatically potentiated UCN-01-induced cell death.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14] Treatment of tumor cells with CHK1 inhibitors enhances signaling through the SRC-RAS-MEK1/2-ERK1/2 pathway and expression of a dominant negative CHK1 protein elevates basal ERK1/2 activity and blocks CHK1 inhibitor-induced ERK1/2 activation. [9][10][11][12][13][14] Interruption of MEK1/2-ERK1/2 pathway by MEK1/2 inhibitors dramatically potentiated UCN-01-induced cell death. 15,16 What is perhaps more of note are findings that non-transformed blood cells, e.g., peripheral mononuclear cells, CD34 + stem cells or primary cultures of human mammary epithelial cells or of rodent hepatocytes were resistant to the CHK1 inhibitor based drug combination toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the RAS/MEK/ ERK pathway is known to be important for cancer cell signaling and survival, MEK targeting may inhibit the growth of some malignant cells resistant to transplant conditioning in the critical early interval after transplantation. Indeed, recent studies of acute myeloid leukemia, 37 multiple myeloma, 38 cutaneous T-cell lymphomas 39 and diffuse large B-cell lymphoma 40 have demonstrated that MEK inhibition may have significant therapeutic value as antineoplastic agents in the setting of hematologic malignancies known to be responsive to allogeneic SCT.…”
mentioning
confidence: 99%